2015
DOI: 10.1080/00207543.2015.1074297
|View full text |Cite
|
Sign up to set email alerts
|

Managing supply disruption through procurement strategy and price competition

Abstract: When facing supply disruptions, the emergency procurement strategy and the optimal allocation procurement strategy are widely used strategies to manage supply risks. In this paper, buyers use these types of procurement strategies under the threat of supply disruption and engage in price competition. The structural properties of the procurement strategies are characterised by their reliability thresholds. We find that reliability thresholds play a critical role in buyer procurement strategy choices, which are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Thus, one failure in the supply chain may lead to other entities failing and may even result in an entire supply chain shutting down (Jüttner and Maklan 2011). While it may be possible to manage disruptions affecting a firm by dispersing purchases across different suppliers (Gupta et al 2015;He et al 2016), that management practice may actually increase the propagation of the disruption at an aggregated level. Therefore, disruptions must be contained before they can affect a larger portion of the supply chain (Chopra and Sodhi 2004;Blackhurst et al 2011;Marley et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, one failure in the supply chain may lead to other entities failing and may even result in an entire supply chain shutting down (Jüttner and Maklan 2011). While it may be possible to manage disruptions affecting a firm by dispersing purchases across different suppliers (Gupta et al 2015;He et al 2016), that management practice may actually increase the propagation of the disruption at an aggregated level. Therefore, disruptions must be contained before they can affect a larger portion of the supply chain (Chopra and Sodhi 2004;Blackhurst et al 2011;Marley et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that supply disruption and procurement times jointly impact the firms' buying decisions. The findings in He, Huang, and Yuan (2016) showed that reliability thresholds play a critical role in buyer procurement strategy choices, which are related to sales price, underage cost, and differentials in unit procurement cost. They explored the effects of reliability levels and costs on equilibrium prices, expected profits, and equilibrium strategy profiles.…”
Section: Product and Process Redundancy: Proactive Stagementioning
confidence: 99%
“…Hou and Zhao [13] made a backup agreement with a penalty scheme between retailers and backup suppliers to mitigate the impact of supply disruption. In the context of supply chain system under supply disruptions, He et al [14] worked out an emergency procurement strategy to manage supply disruption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, scholars [11][12][13][14][15][16][17][18][19][20] did not consider how distributors deliver goods to each other when the supply chain suffers supply disruptions. Furthermore, current studies [11][12][13][14][15][16][17][18][19][20] did not explore the existing switching activities among emergency subsystems.…”
Section: Literature Reviewmentioning
confidence: 99%